LyeTxI-b, a Synthetic Peptide Derived From Lycosa erythrognatha Spider Venom, Shows Potent Antibiotic Activity in Vitro and in Vivo - Reis, Pablo V. M.; Boff, Daiane; Verly, Rodrigo M.; Melo-Braga, Marcella N.; Cortés, María E.; Santos, Daniel M.; Pimenta, Adriano M. de C.; Amaral, Flávio A.; Resende, Jarbas M.; de Lima, Maria E. (Frontiers in Microbiology, 2018)
The antimicrobial peptide LyeTxI isolated from the venom of the spider Lycosa erythrognatha is a potential model to develop new antibiotics against bacteria and fungi. In this work, we studied a peptide derived from LyeTx I, named LyeTxI-b, and characterized its structural profile and its in vitro and in vivo antimicrobial activities. Compared to LyeTxI, LyeTxI-b has an acetylated N-terminal and a deletion of a His residue, as structural modifications. The secondary structure of LyeTxI-b is a well-defined helical segment, from the second amino acid to the amidated C-terminal, with no clear partition between hydrophobic and hydrophilic faces. Moreover, LyeTxI-b shows a potent antimicrobial activity against Gram-positive and Gram-negative planktonic bacteria, being 10-fold more active than the native peptide against Escherichia coli. LyeTxI-b was also active in an in vivo model of septic arthritis, reducing the number of bacteria load, the migration of immune cells, the level of IL-1β cytokine and CXCL-1 chemokine, as well as preventing cartilage damage. Our results show that LyeTxI-b is a potential therapeutic model for the development of new antibiotics against Gram-positive and Gram-negative bacteria.